Relationship of literacy and heart failure in adults with diabetes - Morris Nancy; Laramee Ann S; Littenberg Benjamin (BMC, 2007)
Abstract Background Although reading ability may impact educational strategies and management of heart failure (HF), the prevalence of limited literacy in patients with HF is unknown. Methods Subjects were drawn from the Vermont Diabetes Information System Field Survey, a cross-sectional study of adults with diabetes in primary care. Participants' self-reported characteristics were subjected to logistic regression to estimate the association of heart failure and literacy while controlling for social and economic factors. The Short Test of Functional Health Literacy was used to measure literacy. Results Of 172 subjects with HF and diabetes, 27% had limited literacy compared to 15% of 826 subjects without HF (OR 2.05; 95% CI 1.39, 3.02; P < 0.001). Adjusting for age, sex, race, income, marital status and health insurance, HF continued to be significantly associated with limited literacy (OR 1.55, 95% CI 1.00, 2.41, P = .05). After adjusting for education, however, HF was no longer independently associated with literacy (OR 1.31; 95% CI 0.82 - 2.08; P = 0.26). Conclusion Over one quarter of diabetic adults with HF have limited literacy. Although this association is no longer statistically significant when adjusted for education, clinicians should be aware that many of their patients have important limitations in dealing with written materials.